Application of GNSS Interferometric Reflectometry (GNSS-IR) for Monitoring Tidal Variations in Coastal Zones - Hairul Zulkifli; Danar Guruh Pratomo; Khomsin (Postgraduate, University of Mataram, 2025)
GNSS-Interferometric Reflectometry (GNSS-IR) utilizes Signal-to-Noise Ratio (SNR) data from GNSS satellites to estimate sea level variations. This study applied GNSS-IR using GPS L1 SNR data from four CORS stations (CBEL, CLKI, CHAI, CLMP), paired with their nearest tide gauge stations (BLTG, LBKI, AMHI, LMPA) for validation. Data in RINEX 2.11 format at 30-second intervals were processed, considering antenna heights above the sea surface to extract reflection frequencies. Results indicate strong agreement at the LMPA (r = 0.94, RMSE = 0.17 m) and BLTG (r = 0.90, RMSE = 0.37 m) pairs, demonstrating the reliability of GNSS-IR under favorable conditions. The AMHI pair showed moderate correlation (r = 0.68, RMSE = 0.45 m), while the LBKI pair exhibited no meaningful correlation (r = –0.07), likely due to severe multipath disturbance and local site limitations. These findings suggest that GNSS-IR can provide cost-efficient and accurate sea level estimates, but performance is highly site-dependent and influenced by environmental and instrumental factors. The study highlights the potential of GNSS-IR to complement conventional tide gauges in Indonesia, while emphasizing the need for careful station selection and multi-frequency analysis in future applications.